The Correlation between Learning Motivation Level and Students Learning Outcomes on Science Subjects of Junior High School Class VII - Nurul Afiqah; Restesa Rahmayumita; Aldila Novriandami; M Rahmad; Yennita Yennita (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Student learning motivation is the driving force in students to be able to achieve optimal learning outcomes so that the desired goals of the learning subject can be achieved. The motivation that can come from within the student himself is called intrinsic motivation and comes from outside the student's self or extrinsic motivation. The purpose of this research was to analyze the level of learning motivation of seventh-grade students of SMPN 4 Siak Hulu in science subjects. The method used in this research is a survey method with a quantitative approach. The data collection technique used a learning motivation questionnaire instrument consisting of 25 statement items and the research subject was 67 students. The data analysis technique is through descriptive analysis of the science learning motivation. The research results showed that students' learning motivation was in the high category with a score of 82.45%, while the average learning outcome was 41.1 in the low category. Thus the learning motivation of class VII students of SMPN 4 Siak Hulu is contrary to the learning outcomes obtained by students, so a better learning system is needed to provide solutions or improvements to optimal student learning outcomes by high motivation, especially in science subjects in Class VII SMPN 4 Siak Hulu.